Konseling Pribadi Berbasis Cognitive Behaviour Therapy Untuk Mengatasi Gangguan Kecemasan Mental - Muhammad Adnan Alkatiri; Nurjannah Nurjannah; Neni Simbala (UIN Sunan Kalijaga Yogyakarta, 2021)
This study aims to determine the process and results of counseling conducted by a counselor to a single subject who suffers from acute mental anxiety disorder through personal counseling based on the CBT Cognitive Behavior Therapy technique. The method used in this study is a descriptive qualitative method, namely by explaining the process carried out by counselors when providing counseling to clients who suffer from mental anxiety disorders and the results obtained. The results of the first study obtained were the results of a diagnosis which showed that there were symptoms of mental anxiety based on strange habits that the client often did. These habits are in the form of touching objects around him strangely such as walls, fences, doors and electricity poles repeatedly, washing the body repeatedly more than the amount prescribed by religion when performing ablution, entering and exiting the bathroom several times and tying and removing curtains regularly. unreasonably repeated. Then the second, the counseling process that is carried out is the counselor providing personal counseling to clients by changing the client's anxious feelings through the Cognitive Behavior Therapy approach or replacing the client's irrational thinking that triggers mental anxiety with rational thinking. Furthermore, the third is the result of the counseling process, namely the client has rarely carried out these unnatural habits, even gradually these habits have disappeared.Keyword : Personal Counseling, Cognitive Behavior Therapy, Anxiety